Morphology Evolution, Molecular Simulation, Electrical Properties, and Rheology of Carbon Nanotube/Polypropylene/Polystyrene Blend Nanocomposites: Effect of Molecular Interaction between Styrene-Butadiene Block Copolymer and Carbon Nanotube - Ivonne Otero Navas (Polymers, 2021)
This work studied the impact of three types of styrene-butadiene (SB and SBS) block copolymers on the morphology, electrical, and rheological properties of immiscible blends of polypropylene:polystyrene (PP:PS)/multi-walled carbon nanotubes (MWCNT) with a fixed blend ratio of 70:30 vol.%. The addition of block copolymers to PP:PS/MWCNT blend nanocomposites produced a decrease in the droplet size. MWCNTs, known to induce co-continuity in PP:PS blends, did not interfere with the copolymer migration to the interface and, thus, there was morphology refinement upon addition of the copolymers. Interestingly, the addition of the block copolymers decreased the electrical resistivity of the PP:PS/1.0 vol.% MWCNT system by 5 orders of magnitude (i.e., increase in electrical conductivity). This improvement was attributed to PS Droplets-PP-Copolymer-Micelle assemblies, which accumulated MWCNTs, and formed an integrated network for electrical conduction. Molecular simulation and solubility parameters were used to predict the MWCNT localization in the immiscible blend. The simulation results showed that diblock copolymers favorably interact with the nanotubes in comparison to the triblock copolymer, PP, and PS. However, the interaction between the copolymers and PP or PS is stronger than the interaction of the copolymers and MWCNTs. Hence, the addition of copolymer also changed the localization of MWCNT from PS to PS–PP–Micelles–Interface, as observed by TEM images. In addition, in the last step of this work, we investigated the effect of the addition of copolymers on inter- and intra-cycle viscoelastic behavior of the MWCNT incorporated polymer blends. It was found that addition of the copolymers not only affects the linear viscoelasticity (e.g., increase in the value of the storage modulus) but also dramatically impacts the nonlinear viscoelastic behavior under large deformations (e.g., higher distortion of Lissajous–Bowditch plots).